Dampak Penerapan Absensi Fingerprint Terhadap Implementasi Fungsi Manajemen dan Kinerja - I Wayan Sari; Ida Bagus Raka Suardana (Universitas Pendidikan Nasional, 2017)
ABSTRACTThe aim of this study are 1) to determine the influence of absensi fingerprint to the planning. 2) To determine the influence of absensi fingerprint to organizing. 3) To determine the influence of absensi fingerprint to actuting. 4) To determine of absensi fingerprint to controlling. 5) To determine of absensi fingerprint to employe performance.The result of this research are 1) the influence of fingerprint variabel to the planning is positive significan. 2) The influence of fingerprint variabel to the organizing is positive significan. 3) The influence of fingerprint variabel to the actuating is positif significan. 4) The influence of fingerprint variabel to the controlling is positif significan. 5) The influence of fingerprint variabel to the employe performance is positifsignifican.The researcher recommendation to the Puskesmas sidemen which become research location are to Puskesmas Sidemen?Leader to incrise absensi fingerprint program to mantanance employe performance by crosscek absensi date every week. Biside those one the result of this research have beenuse to base on future research. This reaserch use kwalitatif and kwantitatifmethode by survey and get from all Puskesmas sidemen employ by give them instrument reaserch (quisioner) and take from Puskesmas Sidemen regulation.Data analyse use PLS (Partial Least Square) who isnot use distrubusi normal date.